La prescripción de la facultad para determinar infracciones administrativas - Mendoza Antonioli, Dante (2021)
The author develops four problems of interpretation of the national regulation regarding the prescription of the sanctioning power of the State, presenting the development that each one of them has deserved in the time of validity of Law No. 27444, Law of General Administrative Procedure.